2010
DOI: 10.1016/j.molcel.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Antagonism between JMJD2A/KDM4A and HP1γ during Cell Cycle Progression

Abstract: The KDM4/JMJD2 family of histone demethylases is amplified in human cancers. However, little is known about their physiologic or tumorigenic roles. We have identified a conserved and unappreciated role for the JMJD2A/KDM4A H3K9/36 tridemethylase in cell cycle progression. We demonstrate that JMJD2A protein levels are regulated in a cell cycle-dependent manner and that JMJD2A overexpression increased chromatin accessibility, S phase progression, and altered replication timing of specific genomic loci. These phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
162
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 46 publications
13
162
0
Order By: Relevance
“…It has been suggested that the JMJD2A histone demethylase plays a major role in the regulation of apoptosis. Specifically, several studies have demonstrated that the depletion of JMJD2A increases p53-dependent apoptosis (41)(42)(43). The findings of the present study showing a substantial reduction in JMJD2A protein expression concomitant with an increase in p53 protein levels in the DFO-treated MCF-7 cells are in accord with this suggestion.…”
Section: Mcf-7supporting
confidence: 91%
“…It has been suggested that the JMJD2A histone demethylase plays a major role in the regulation of apoptosis. Specifically, several studies have demonstrated that the depletion of JMJD2A increases p53-dependent apoptosis (41)(42)(43). The findings of the present study showing a substantial reduction in JMJD2A protein expression concomitant with an increase in p53 protein levels in the DFO-treated MCF-7 cells are in accord with this suggestion.…”
Section: Mcf-7supporting
confidence: 91%
“…Recently, Black and colleagues (Black et al 2010) demonstrated that CBX3, along with a histone demethylase, plays a role in cell cycle regulation in Caenorhabditis elegans and human cells. Additionally, CBX3 has been implicated in controlling levels of primordial germ cells (PGCs) in mouse embryos via cell cycle regulation and apoptosis (Abe et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KDM4A plays a critical role in genome replication and stability (6,47). Overexpression of KDM4A leads to accelerated passage through S phase, correlating with increased chromatin accessibility, in human cells, while mutation of the Caenorhabditis elegans KDM4A ortholog leads to reduced rates of S phase and DNA damage (6).…”
mentioning
confidence: 99%